Status and prospects of digital legislation development - O. A. Makarova; A. D. Makarov (Russian Journal of Economics and Law)
Objective: to analyze the totality of normative legal acts regulating public relations in the sphere of digital technologies and digital legislation, to determine the legal methods of regulating these relations, as well as the prospects for the digital legislation development.Methods: a formal legal approach, as well as a method of literal interpretation of the provisions of the current legislation. Since digitalization as the introduction of digital technologies in various spheres of life helps to make decisions, on the one hand, without human participation, but, on the other hand, affecting many aspects of social life (healthcare, culture, education, labor, etc.), the study used communicative and anthropological approaches from the viewpoint of assessing the digital legislation impact on human rights and the legitimate rights and interests of citizens, as well as information perception of the digital legislation norms.Results: based on the analysis of normative legal acts regulating public relations in the field of digital technologies, a conclusion is made about the formation of digital legislation as a complex branch of legislation of the new digital reality that regulates social relations in the field of numbers, algorithms, big data, etc. The authors revealed that in the process of regulating relations in the field of digital technologies the legislator uses different methods: stimulating, limiting, dispositive. It is proposed to consider digital legislation as a functional legislation that ensures the implementation of the norms of other branches of legislation: investment legislation (attracting investments through an investment platform), legislation in the field of financial services and securities market, legislation in the field of medical services, etc.Scientific novelty: the article formulates the concept of digital legislation, which is understood as a complex legislation that combines the norms of private and public law and defines the methods of regulating relations arising in the field of digital technologies.Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activities, as well as in the practice of applying the norms of digital legislation.